Factors of future teachers' motivation formation for the physical improvement - Нікула , Наталя Вікторівна, Natalia, Hakman, A., Andrieieva, O., Kashuba, V., Bezverkhnia, H., Tsybulska, V., Maievskyi, M., Osadchenko, T., Semenov, A., Kljus, O., Tsiuniak, O. Nikula (Baltic Journal Of Health And Physical Activity, 2021)
T‪he article uses factor analysis to obtain an insight into the peculiarities of the motivation for physical improvement of students from the Faculty of Primary Education with different modes of attendance.
Keywords: motivation, future teachers, factors, physical improvement